A Neo-Humean Analysis of Turkish Enclitic “dE” in Coherence Relations / Türkçe’deki “dE” Enklitiğinin Tutarlık İlişkilerinin Neo-Humean Analiz Yöntemine Göre İncelenmesi - Duruk, Eda (Journal of History Culture and Art Research, 2018)
Abstract This quantitative study aims to investigate the role of enclitic dE in Turkish coherence relations by depending on Kehler's (2002) taxonomy. It also explores the applicability of the taxonomy with regard to its relevance for the analysis of written-text discourse and focusing dE in Turkish. He proposed three main categories such as Resemblance, Cause-Effect, and Contiguity. The first category was divided into subcategories as Similarity, Contrast, Exemplification, Generalization, Exception, and Elaboration. The subcategories of the second one were listed as Result, Explanation, Violated Expectation, and Denial of Preventer. The last category was noted to include Occasion. While gathering data, tokens of dE were extracted from naturally occurring written-discourse gathered from a novel titled “Türkan Tek ve Tek Başına”. These were selected as representatives of the target item's use in Turkish and discourse context was taken into consideration. The frequency count showed that the most common relations are Occasion, Parallel (Similarity), and Result relations. It was concluded that enclitic dE could establish coherence relations within the text in many different ways. The results shed some light onto the understanding of what kind of coherence relations this enclitic contribute to in written discourse. Öz Bu nicel çalışmanın amacı Türkçe’deki dE enklitiğinin tutarlık ilişkisini Kehler’in (2002) taksonomisine göre incelemektir. Kehler şu ana kategorileri önermiştir: Benzerlik, Sebep-Sonuç ve Bitişiklik. İlk kategori Benzerlik, Zıtlık, Örnekleme, Genelleme, Hariç tutma ve Detaylandırma olarak alt gruplara ayrılmaktadır. İkinci kategorinin altında ise Sonuç, Açıklama, Gerçekleşmemis Beklenti ve Sebebi Çürütme grupları vardır. Zaman da son kategoriyi oluşturmaktadır. Veriyi toplarken ayrı yazılan dE bağlacı ile ilgili örnekler doğal söylem örneklerinden alınmıştır. Bunların hedef yapının Türkçe’deki kullanımını temsil ettiği öngörülmüştür ve söylem bağlamı göz önünde bulundurulmuştur. Sıklık sayımı en fazla kullanılan ilişkilerin Zaman, Benzerlik ve Sonuç ilişkileri olduğunu göstermiştir. Sonuç olarak dE enklitiğinin birçok farklı tutarlık ilişkisi kurabileceği sonucuna varılmıştır. Çalışmanın sonuçları bu enklitiğin yazılı söyleme tutarlık ilişkileri açısından neler kattığınının anlaşılmasına ışık tutmaktadır.